Modulation of spin effect in electronic and vibrational properties of terbium dihydride (TbH2): An ab-initio study. (18th March 2020) - Patel, Komal; Raval, Dhara; Babariya, Bindiya; Gupta, Sanjeev K.; Gajjar, P.N.
Abstract: The interaction of hydrogen with terbium was correlated and the structural and electronic structure properties for the cubic rare earth terbium dihydride (TbH2 ) using density functional theory (DFT) have been studied. The electronic band structure and density of states (DOS) for spin-up, spin-down and non-spin cases were studied and furthermore influence of higher pressure was also investigated. The charge contribution shows that TbH2 has metallic characteristic with a mixed covalent and ionic bonding. The Fermi surfaces show hole type structure and provide a space where hydrogen can be absorbed and filled easily. The Löwdin population analysis show that the decrease in charge density of Tb atom which explain absorption of H atom by Tb. The charge density of TbH2 also show decrease in differential charge density which verify the Löwdin population analysis. Furthermore, we have also analysed phonon dispersion curve at ambient and higher pressure and changes were studied. The TbH2 can be a good alternative to develop a hydrogen storage device as mass ratio percentage is around 1.27%. Highlights: We have studied the structural, electronic and vibrational properties of terbium dihydride (TbH2 ) at ambient and higher pressure. Hydrogen storage capacity depend on pressure is explain by electronic band structure and density of state. The soften mode in phonon dispersion curve at higher pressure show structural phase transition. Löwdin population is also analyzing to determine the distribution of electron among the constituent atoms.